Back Cover: Development of a database strategy based on liquid chromatography–quadrupole time‐of‐flight mass spectrometry for the screening of 75 estrogenic chemicals from treated sewage effluent. Issue 8 (5th August 2021) - Yagishita, Mayuko; Kubo, Takuya; Otsuka, Koji; Nakayama, Shoji F.; Nakajima, Daisuke
Abstract : DOI: 10.1002/sscp.202100015 The cover picture shows pathway to real estrogenic chemicals from the treated sewage effluent using two databases. These databases are respectively applied for a rough screening and precise identification of the estrogenic chemicals of sewage effluents as follows: step 1) A treated sewage effluent sample is subjected to analysis using the time‐of‐flight scan mode, and a rough screening using DATABASE I is performed. step 2) The obtained candidate estrogenic chemicals by step 1 are measured using the targeted MS/MS mode in which collision energy dependence fragmentations of them are induced. The resulting fragmentation mass spectra are screened using DATABASE II.